GLOBAL MOBILITY: BIBLIOMETRIC APPROACH - Tjipto, Michelle Caroline; Ariani, Mintarti; Pratono, Aluisius Hery (Program Sarjana Manajemen Universitas Internasional Batam, 2024)
The research seeks to understand the complex interactions between migration, population relocation, and climate change in today's dynamic global terrain. It explores changing trends, drivers, and repercussions of modern migration in the context of environmental changes using extensive data analysis. Notably, the research investigates new cyber migration tendencies, emphasizing the link between human movement and technology. It also examines how international student mobility affects global knowledge networks and talent migration. In addition, the study looks at both forced and voluntary migration, considering factors including environmental change, war, and socioeconomic differences.